Penerapan Sistem Akuntansi Penerimaan Kas Pada Badan Amil Zakat Nasional Provinsi Jawa Timur (Laporan Kegiatan Kuliah Kerja Lapangan) - Putri Puspita Sari; Tjandra Wasesa; Heri Toni; Sutini Sutini; Diana Zuhro (Universitas 45 Surabaya, 2023)
The amil zakat agency in preparing financial statements must be guided by the Statement of Accounting Standards (PSAK) 109 concerning the accounting of Zakat, Infaq, and Alms (ZIS) which was ratified on April 2010 and became effective on January 1, 2012. PSAK 109 regulates the recognition, measurement, presentation and disclosure of Zakat, Infaq, and Alms (ZIS) transactions. One of the discussions in PSAK 109 Today's technological progress is accelerating, requiring various groups to continue to make changes, especially in meeting information needs. Get it fast and akura. Fast and accurate information will help in planning, control and decision making. One of the needs of information management is financial information that is actually packaged practically with the help of computers. In today's era, computers are tools that can support the progress of the company. Computers can help solve problems in management, computing, data security, system creation, and decision making, and nowadays computers are increasingly used by all kinds of companies, not only big ones but also small ones are starting to use them. Many companies use computers to process company accounting data.